Infantile bullous pemphigoid: A Rare immunobullous disease where tzanck test is a valuable diagnostic aid - Mahmud, Md Mostaque; Biswas, Sanchita; Paul, Debatosh (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Abstract not available BSMMU J 2022; 15(1): 57-60